Intraoperative Suspicion of Squamous Cell Carcinoma in a Presumed Giant Scalp Cyst: A Case Report - Şükrü Kasap; Muhammed Said Aydin; Gökay Özler; Mustafa Nişancı (Izmir Katip Celebi University Faculty of Medicine, 2026)
Squamous cell carcinoma (SCC) arising in an epidermal cyst is rare and may be overlooked when a large scalp lesion appears clinically benign. An elderly woman presented with a 19 × 8 cm occipital mass thought to be a giant cyst. Ultrasonography and computed tomography showed a predominantly cystic lesion with internal solid components, but the overlying skin had no obvious malignant features. During surgery, abnormal tissue was noted over the lesion, in the subdermal plane, and at its base. The planned cyst excision was therefore converted to an oncological resection that included the overlying skin and underlying periosteum. Long-standing expansion had produced enough tumor-free scalp laxity for primary closure without a flap or skin graft. Histopathology showed well-differentiated acantholytic SCC arising in an epidermal cyst, with clear margins. Healing was uneventful, and at 1 year the scalp remained stable without clinical recurrence. Large or heterogeneous scalp cysts, particularly those with solid components, warrant careful assessment. Unexpected intraoperative findings should prompt immediate reconsideration of the surgical plan and complete histopathological evaluation.